Influence Disclosure, Tenure Audit, Audit Judgment and Lowballing on the Accuracy of Giving Audit Opinions to Hoods in Makassar - Syamsuri Rahim; Muslim Muslim; Andi Fajri Bahnur (Jurnal Info Sains : Informatika dan Sains, 2023)
This study aims to examine the effect of disclosure, audit tenure, audit judgment and lowballing on the accuracy of providing audit opinion in KAP in Makassar. Data in this study were obtained from each KAP in Makassar City who were willing to become respondents. This research uses primary data by conducting research directly in the field by giving questionnaires / question sheets to 41 respondents. The data analysis method used is multiple linear regression analysis. The results showed that: partially, the Disclosure variable had a positive and significant effect on the Accuracy of Audit Opinion, the Tenure Audit variable had a positive and significant effect on the Accuracy of Audit Opinion, Audit Judgment Positive and significantly affected the Accuracy of Audit Opinion and Lowballing. on the Accuracy of Providing Audit Opinions.